On expansivity of Uniform Dynamical Systems - Ihsan Jabbar Khadim; Abbas, Ansam (Al-Qadisiyah Journal of Pure Science, 2020)
In this study we introduce and study on expansivity of uniform dynamical systems, we obtain various important properties and theorems about sensitivity and expansivity of uniform continuous maps.